A sensitive quantification of the peptide apidaecin 1 isoforms in single bee tissues using a weak cation exchange pre-separation and nanocapillary liquid chromatography coupled with mass spectrometry - Danihlík, Jiří; Šebela, Marek; Petřivalský, Marek; Lenobel, René (Journal of chromatography. A, 2014)
Apidaecins represent an important group of antimicrobial peptides occurring in honey bee hemolymph, where they play an important role as key components of humoral immunity. The present study demonstrates the development of a highly sensitive assay for apidaecin 1 isoforms quantification in the hemolymph or body parts from honey bee individuals. The analytical protocol comprises apidaecins 1 purification and enrichment steps by weak cation-exchange chromatography (WCX) in laboratory-made WCX-Tip microcolumns combined with a desalting step on a reversed-phase sorbent (C8) carried in StageTips. Apidaecin-enriched fraction was analyzed by a reversed-phase based nanoliquid chromatography (C4) separation coupled with high-resolution mass spectrometry. The method performance was validated in its specificity, linearity (0-5pmol), recovery (∼45%), precision (<10% at 0.1pmol), limit of detection (∼50fmol), limit of quantification (0.1pmol) and sample stability. The method was successfully applied to analyze the content of apidaecin 1 isoforms in the following samples: hemolymph - 13.0ng/μL (95% confidence interval of 7.5-18.6ng/μL), thoraxes - 36.2ng/unit (95% CI of 18.9-53.6ng/unit) and heads - 12.9ng/unit (95% CI of 9.1-16.7ng/unit). Freshly emerged bees had apidaecin 1 isoforms levels below the limit of detection. Thus it was possible to use them as a competitive matrix for calibration standards to prevent losses of highly basic apidaecins. This new protocol for apidaecin 1 isoforms quantification represents a promising tool to study the role of apidaecins in honey bee immunity and can be considered as a proof-of-concept for the development of sensitive quantification methods for basic antimicrobial peptides in various organisms.
Keywords: Limit of Detection; Honey bee; hmotnostní spektrometrie; Protein Isoforms; včely; Apidaecin; Mass Spectrometry; Mass spectrometry; Animals; zvířata; vysokoúčinná kapalinová chromatografie; Antimicrobial Cationic Peptides; Nanoflow liquid chromatography; kalibrace; limita detekce; Calibration; Quantification; kationty; Chromatography, High Pressure Liquid; Cations; Bees; kationické antimikrobiální peptidy; protein - isoformy; Antimicrobial peptide